RANCANG BANGUN APLIAKSI PENJUALAN IKAN LAUT BERBASIS ANDROID - Kharisma Rizki Adhy Adhy; Muh. Fadli Hasa; Ermin (Framework : Jurnal Ilmu Komputer dan Informatika, 2022)
The Jembatan Puri Fish Auction is one of the largest auctions located in the city of Sorong. This auction is the only place where loading and unloading activities start from fishermen, charts, and fishing vessels that are still searching around the waters of the city of Sorong, the auction is an access for fish to enter the city of Sorong. The purpose of this research is to build an android and web-based fish selling application, which is expected to help Andy78's SMEs to increase sales of the products they sell. the method used in building this sales application is using Extreme Programming (XP). This fish selling application was built using the Java programming language to build Android-based models and implementations using Android Studio for making applications and using the PHP programming language for web-based creation, and using a MySQL database as data storage. The results obtained in this study are an android and web-based fish selling application that can have a good impact and make it easier for Andy78 SMEs to carry out the buying and selling process that takes place.